Preclinical in vitro and in vivo evidence for targeting CD74 as an effective treatment strategy for cutaneous T-cell lymphomas - Costanza, Mariantonia; Giordano, Catello; von Brünneck, Ann-Christin; Zhao, Jing; Makky, Ahmad; Vinh, Katharina; Montes-Mojarro, Ivonne Aidee; Reisinger, Florian; Forchhammer, Stephan; Witalisz-Siepracka, Agnieszka; Edtmayer, Sophie; Stoiber, Dagmar; et al. (British journal of dermatology, 2025)
Prognosis and quality of life in patients with advanced cutaneous T-cell lymphoma (CTCL), particularly in those with Sézary syndrome (SS) or advanced-stage mycosis fungoides (MF), are poor. Monoclonal antibodies or antibody-drug conjugates (ADCs) have been added into CTCL treatment algorithms, but the spectrum of antibody-targetable cell surface antigens in T-cell non-Hodgkin lymphomas (T-NHLs) is limited.To evaluate the expression of the major histocompatibility complex class II chaperone CD74 in common subtypes of CTCL by various methods, and to explore the efficacy of targeting CD74 in CTCL cells with an anti-CD74 ADC in vitro and in vivo.We comprehensively investigated the expression of CD74 in well-defined CTCL cell lines by polymerase chain reaction, immunoblotting and flow cytometry. More than 140 primary CTCL samples of all common subtypes were analysed by immunohistochemistry, flow cytometry, immunofluorescence and ‘co-detection by indexing’ (CODEX) multiplexed tissue imaging, as well as by single-cell RNA sequencing (scRNAseq) analyses. DNA methylation of CTCL cell lines was interrogated by the generation of genome-wide methylation profiling. The effect of a maytansinoid-conjugated humanized ADC against CD74 was investigated in CTCL cell lines in vitro, alone or in combination with gemcitabine, and in vivo after xenotransplantation of CTCL cell lines in NOD-scid Il2rgnull mice.We demonstrated that CD74 is widely and robustly expressed in CTCL cells. In addition, CD74 expression in SS and MF was confirmed by scRNAseq data analysis and was correlated in CTCL cell lines with CD74 DNA hypomethylation. CD74 was rapidly internalized in CTCL cells and CD74 targeting by the ADC STRO-001 efficiently killed CTCL-derived cell lines. Finally, targeting of CD74 synergized with conventional chemotherapy in vitro and eradicated murine xenotransplants of CTCL cell lines in vivo.CD74 is expressed in common CTCL subtypes. Targeting CD74 efficiently killed CTCL cells in vitro and in vivo. We therefore suggest the targeting of CD74 to be a highly promising treatment strategy for CTCL.Cutaneous T-cell lymphoma (or ‘CTCL’) is a rare cancer that begins in certain types of blood cells. CTCL belongs to a group of cancers called ‘T-cell non-Hodgkin lymphomas’. It occurs most often in the skin. In Europe, CTCL affects about 0.5 people in 100,000 every year. It is more common in the USA. Even though CTCL is rare, better treatments are needed. Early-stage CTCL can be treated, but the effect of treatment does not last long. The quality of life and life expectancy of people with advanced CTCL is poor. The disease can be treated with molecules called ‘antibody drug conjugates’ (‘ADCs’ for short). ADCs are special proteins designed to recognize and attach to the surface of cancer cells.In our study, carried out by researchers across Germany and Austria, we identified a protein called ‘CD74’ on the surface of CTCL cells. We found it to be a promising target for treatment. Our experiments demonstrated that ADCs that target CD74 could effectively kill CTCL cells.Our findings suggest that targeting CD74 could be developed into a new treatment approach for CTCL, potentially leading to clinical trials.
Online veröffentlicht: 27. Februar 2025
Gesehen am 12.06.2025